2015
DOI: 10.1002/mabi.201500253
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Fringed Platforms Produced by Laser Interference for Aligned Neural Cell Growth

Abstract: Ordering neural cells is of interest for the development of neural interfaces. The aim of this work is to demonstrate an easy-to-use, versatile, and cost/time effective laser-based approach for producing platforms that promote oriented neural growth. We use laser interferometry to generate fringed channels with topography on partially reduced graphene oxide layers as a proof-of-concept substrate. We study cell adhesion, morphology, viability, and differentiation in cultures of embryonic neural progenitor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Compared to most reported graphene-based patterns on certain substrates via other techniques, the reported laser-scribed process of 3D graphene-based micropatterns can selectively and precisely tune GO to rGO conversion and pattern GO–rGO–GO structures, which benefit to utilize the different properties (conductivity, hydrophilicity, adsorptivity) of GO and rGO for potential applications in electronics, biomedicine, and energy. The current repurposing laser-scribing approach provides a standard, general, and robust platform for micro/nanofabrication in a time- and cost-effective manner and can be easily extended to produce and pattern various graphene hybrids (such as polymer/graphene, metal nanostructures/graphene hybrids), other emerging nongraphene 2D materials, and their hybrids, which will fulfill the requirements to amend capability of graphene devices and fit them into more applications in various fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to most reported graphene-based patterns on certain substrates via other techniques, the reported laser-scribed process of 3D graphene-based micropatterns can selectively and precisely tune GO to rGO conversion and pattern GO–rGO–GO structures, which benefit to utilize the different properties (conductivity, hydrophilicity, adsorptivity) of GO and rGO for potential applications in electronics, biomedicine, and energy. The current repurposing laser-scribing approach provides a standard, general, and robust platform for micro/nanofabrication in a time- and cost-effective manner and can be easily extended to produce and pattern various graphene hybrids (such as polymer/graphene, metal nanostructures/graphene hybrids), other emerging nongraphene 2D materials, and their hybrids, which will fulfill the requirements to amend capability of graphene devices and fit them into more applications in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…Some interesting attempts have been made to utilize graphene-based micropatterns (such as fluorinated , graphene lines, , rGO lines, , GO grooves, lines, and grids) with dimensions ranging from several tens to several hundred micrometers fabricated via conventional lithographic and laser irradiation techniques as a promising platform and cell-guiding physical cues for controlling cell adhesion, alignment, ,, differentiation, and gene delivery, which have great potential in biomedical applications (such as tissue engineering) . Regrettably, these techniques are too complex to produce low-cost, scalable graphene-based patterns, which greatly impedes the translation of interesting findings relating control of cell behavior into practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous reports have shown that grid micropatterned ECM proteins could promote neuronal differentiation of NSCs, while square pattern promoted the formation of glial cells . Graphene‐patterned substrates have been developed to enhance cell adhesion, neurite outgrowth, alignment, and neural differentiation …”
Section: Graphene‐based Scaffolds For Neurogenesis and Myogenesismentioning
confidence: 99%
“…The interesting preferential cell adhesion on graphene stripes might result from the better deposition of PDL precoating, as atomic force microscope characterization clearly indicated a thicker PDL layer on graphene coated region than bare glass surface. Similarly, Pelaez et al used a laser interferometry method to fabricate PDL coated rGO substrates with fringed patterns (a period of 9.4 µm), which promoted the neurite alignment of rat embryonic neural progenitor cells (ENPCs) compared to nonpatterned graphene surface. Recently, a one‐step strategy was developed by Lee et al to prepare patterned graphene based films via infrared based photothermal reduction on GO films, which contain both rGO regions with high conductivity and unique topographical roughness and also GO regions for potential functionalization .…”
Section: Graphene‐based Scaffolds For Neurogenesis and Myogenesismentioning
confidence: 99%
“…Optical fabrication of grid structures for growing linear neurons has been demonstrated via laser ablation in graphene [ 182 ] and laser interference reduction of GO. [ 183 ] Figure 7d shows a schematic description of this process. Single layer graphene (SLG) on glass is etched by a pulsed laser to create graphene strips (left).…”
Section: Applications Of Optically Modified 2d Materialsmentioning
confidence: 99%